Conductive hybrid filaments of carbon nanotubes, chitin nanocrystals and cellulose nanofibers formed by interfacial nanoparticle complexation. (June 2020) - Zhang, Kaitao; Ketterle, Lukas; Järvinen, Topias; Hong, Shu; Liimatainen, Henrikki
Abstract: In this paper, anionic TEMPO-oxidized cellulose nanofibers (TO-CNFs) and cationic, partially deacetylated, chitin nanocrystals (ChNCs) were used to fabricate continuous composite filaments (TO-CNF/ChNC filament) with a straightforward and sustainable aqueous process based on the interfacial nanoparticle complexation (INC) of oppositely charged nano-constituents. In particular, the role of TO-CNF and ChNC concentrations in filament drawing and the effect of drawing speed on the mechanical properties of composite filaments were investigated. Moreover, conductive filaments were fabricated by mixing single walled carbon nanotubes (SWCNTs) with TO-CNF dispersion and further complexing with the ChNC aqueous suspension. A conductive filament with an electrical conductivity of 2056 S/m was obtained. However, the increase in the SWCNTs content reduced the mechanical properties of the formed filament compared to neat TO-CNF/ChNC filament. This study not only introduces a new nanoparticle candidate to prepare filaments based on INC method but also provides potential advanced and alternative green filament to be used as wearable electronics in biomedical area. Graphical abstract: Unlabelled Image Highlights: Interfacial nanoparticle complexation was employed to draw filament. Bio-based filaments were prepared using cationic chitin nanocrystal and anionic naoncellulose as raw materials. The influence of drawing speed on the tensile strength was investigated. Conductive filament with single walled carbon nanotubes was fabricated using interfacial nanoparticle complexation.